2010
DOI: 10.1103/physreva.82.045806
|View full text |Cite
|
Sign up to set email alerts
|

Effect of buffer gas on an electromagnetically induced transparency in a ladder system using thermal rubidium vapor

Abstract: We report on the first observation of electromagnetically induced transparency (EIT) in a ladder system in the presence of a buffer gas. In particular we study the 5S 1/2 -5P 3/2 -5D 5/2 transition in thermal rubidium vapor with a neon buffer gas at a pressure of 6 Torr. In contrast to the line narrowing effect of buffer gas on Λ-systems we show that the presence of the buffer gas leads to an additional broadening of (32 ± 5) MHz, which suggests a cross section for Rb(5D 5/2 )-Ne of σ−19 m 2 . However, in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 24 publications
1
15
0
3
Order By: Relevance
“…This EIT resonance has a linewidth of 2π × (3.4 ± 0.3) MHz, which is larger than the ≈2π × 1 MHz single-atom EIT linewidth given by γ EIT = 2 c /γ [18], where c is the Rabi frequency of the coupling field and γ is the 5P 3/2 state linewidth. The observed EIT linewidth is likely increased by laser linewidths and transit-time broadening [18,19], however in our experiment the broadening is mostly due to the drift of the probe laser frequency over the course of one data-averaging sequence.…”
Section: Methodsmentioning
confidence: 59%
“…This EIT resonance has a linewidth of 2π × (3.4 ± 0.3) MHz, which is larger than the ≈2π × 1 MHz single-atom EIT linewidth given by γ EIT = 2 c /γ [18], where c is the Rabi frequency of the coupling field and γ is the 5P 3/2 state linewidth. The observed EIT linewidth is likely increased by laser linewidths and transit-time broadening [18,19], however in our experiment the broadening is mostly due to the drift of the probe laser frequency over the course of one data-averaging sequence.…”
Section: Methodsmentioning
confidence: 59%
“…However, this value can be further improved whenever the techniques related to resonance-width reduction are implemented. Examples of these techniques include a use of paraffin-coated cell [21] and a buffer gas added to the interaction cell [20,21] (except for the effect observed in the Ξ-type interaction, where the buffer gas has been reported to increase the resonance width [24]). Note that the earlier studies have reported the resonance width of up to 20 times smaller than the natural width for D 2 in 87 Rb, using a Laguerre−Gaussian coupling beam [25] and an appropriate beam intensity [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…Examples of these techniques include a use of paraffin-coated cell [21] and a buffer gas added to the interaction cell [20,21] (except for the effect observed in the Ξ-type interaction, where the buffer gas has been reported to increase the resonance width [24]). Note that the earlier studies have reported the resonance width of up to 20 times smaller than the natural width for D 2 in 87 Rb, using a Laguerre−Gaussian coupling beam [25] and an appropriate beam intensity [24,25]. When all of our 'narrowing' techniques are implemented, the experimental method of ours can be used to build a robust and stable magnetometer using Zeeman sub-levels [26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…This is largely because of the difficulty of detecting the mid-IR radiation, which is strongly absorbed in conventional Rb cells. We note that similar energy level configurations in Rb atoms have been used extensively for studying ladder-type electromagnetically induced transparency [15,16], nonlinear properties of four-wave mixing and new field generation [17,18], atomic coherence effects [19,20] and transfer of orbital angular momentum [3,21], as well as for imaging of ultracold atoms [22].…”
Section: Figurementioning
confidence: 99%